Urgensi Perlindungan Hukum Hak Cipta Atas Karya Yang Dihasilkan Oleh Artificial Intelligence (Ai) Di Indonesia - Afinda Margaretha; Risma Sari Cantik Juliatin; Dimas Pramodya Dwipayana (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The development of Artificial Intelligence (AI) has significantly transformed the process of creating works in the fields of art, literature, and design. AI is now capable of generating works autonomously without direct human involvement in the creative process. This situation raises legal issues, particularly regarding copyright protection in Indonesia, which is still based on the concept of a human creator as stipulated in Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. This study aims to analyze the urgency of legal protection for AI-generated works and to examine the existing legal gaps. The method used is a normative juridical approach, analyzing relevant laws and legal concepts. The results indicate that the absence of specific regulations on AI-generated works creates legal uncertainty concerning ownership and copyright protection. Therefore, legal reform or progressive interpretation is necessary to provide legal certainty, encourage innovation, and protect the interests of parties involved in the development and use of AI. This study concludes that legal protection for AI-generated works is an urgent necessity in order to align Indonesia’s legal system with the advancement of digital technology.